(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2023)
The problem of violence in schools causes considerable concern in many countries of the world and in our country as well because of the enormous psychological and physical consequences it brings to children and young people. In literature, research can be found even forty years ago, when this phenomenon was defined as aggressive, deliberate, and persistent action carried out by a group or individual against a victim who cannot be easily defended. More recently, violence is not only considered to be physical, but also violence can also be experiences through social networks, which gives us an additional incentive for its further study, all in order to stand in the way of violence and reduce it as much as possible. This paper studies the theoretical and empirical knowledge about some significant factors that contribute to the occurrence of peer violence, such as: family, school environment and personality characteristics of the bully and the victim. At the end, an overview of effective violence prevention programs from different countries in the world is given.